2021
DOI: 10.1002/ente.202100889
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Halide Perovskite‐Based Electrochemical Supercapacitors: Recent Progress and Perspective

Abstract: Hybrid halide perovskites have become highly popular mixed electronic−ionic material over the past decade due to a wide range of applications in flexible optoelectronics especially for energy conversion and light‐emitting devices. While ion migration in these materials is the main cause of device instability under heat and light, this property can make them ideal for energy storage applications such as Li‐ion batteries, photorechargeable batteries, and supercapacitors. Herein, progress so far in the field of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…In HHP-based capacitors, the diffusion mechanism is due to the intercalation/deintercalation process of liquid electrolytic ions into perovskite sites, and the EDLC process is due to the electrostatic accumulation of charges at the electrode−electrolyte interface and at pore boundaries; we refer to our previous published works for more details on charge storage mechanisms. 33,34,38 In fact, the b parameter in the perovskite-based supercapacitor exceeds unity at a low field regime (<0.2 V) (Figure 2D) due to strong electron−ion coupling. We have observed that the increasing carbon content in the perovskite matrix reduces the b value.…”
Section: Resultsmentioning
confidence: 99%
“…In HHP-based capacitors, the diffusion mechanism is due to the intercalation/deintercalation process of liquid electrolytic ions into perovskite sites, and the EDLC process is due to the electrostatic accumulation of charges at the electrode−electrolyte interface and at pore boundaries; we refer to our previous published works for more details on charge storage mechanisms. 33,34,38 In fact, the b parameter in the perovskite-based supercapacitor exceeds unity at a low field regime (<0.2 V) (Figure 2D) due to strong electron−ion coupling. We have observed that the increasing carbon content in the perovskite matrix reduces the b value.…”
Section: Resultsmentioning
confidence: 99%
“…The perovskite structure, [1] with its almost infinitely adaptable array of derivatives, must count as one of the most important in materials science with the essential ABX 3 (A = a large cation; B = a smaller cation; X = an anion) structural archetype contributing to ferroelectric, [2] piezoelectric, [3] superconducting, [4] photochemical, [5] and many other technologically important properties. Interest in perovskites has recently been further accelerated by rapid developments in the fabrication of hybrid [3,[6][7][8] or all-inorganic halide perovskite ABX [9,10] structures where A is an organic or alkali metal counterion, B typically lead or tin, and X a halogen, allowing materials with optical and photovoltaic characteristics [11,12] exploitable in solar cells, [13,14] ion-conducting materials, [15] supercapacitors, [16] and other energy storage devices [17] to be developed. Bulk halide perovskites are however reactive, suffering from surface hydration, [18] phase transformations, [19,20] and high defect densities, [21] reducing their performance and longevity.…”
Section: Introductionmentioning
confidence: 99%
“…We have also investigated the ionic-electronic interaction under different operating conditions leading to tunable ambipolarity of perovskites 26 and tuning the ionic conductivity by modulating the A-site cation and X-site halide ions in the perovskites 27 using a similar device architecture. Moreover, understanding the photo physics at perovskite–electrolyte interface can be useful in the application of hybrid perovskites in photo-rechargeable electrochemical cells 28 , electrolyte gated field effect transistors (FETs) 29 , photoelectrochemical (PEC) and photocatalytic (PC) cells for water-splitting 30 , supercapacitors 28 , 31 and CO 2 capture and reduction devices 32 . However, the precise interplay between ion movement and electronic kinetics in these devices presents a challenge for optimizing these devices.…”
Section: Introductionmentioning
confidence: 99%